2016
DOI: 10.31235/osf.io/4dymx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Widening Gender Gap in Opposition to Pornography, 1975-2012

Abstract: In the last several decades pornography in the U.S. has become more mainstream, more accessible, more phallocentric and more degrading to women. Further, consumption of pornography remains a major difference in the sexual experiences of men and women. Yet research has not addressed how opposition to pornography has changed over the this period, despite shifts in the accessibility and visibility of pornography as well as new cultural and legal issues presented by the advent of Internet pornography. We examine g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…While pornography use in general predicts lower marital quality later on regardless of whether the users are violating their own moral views, viewing pornography at higher frequencies while contradicting one's moral values may potentially take a toll on relationship quality. As attitudes toward pornography become more accepting in the United States (Lykke & Cohen, 2015;Price, Patterson, Regnerus, & Walley, 2016), it is possible that any moderating effect of moral incongruence will be attenuated. Conversely, if the attitudes of young Americans toward pornography are not changing tremendously (see Price et al, 2016) even as pornography use continues to increase, it may be that more Americans will find themselves in the situation where they are violating their own consciences in viewing pornography, thus holding greater consequences for mental health (Grubbs et al, 2015b;Perry, 2017b) or intimate relationships.…”
Section: Discussionmentioning
confidence: 99%
“…While pornography use in general predicts lower marital quality later on regardless of whether the users are violating their own moral views, viewing pornography at higher frequencies while contradicting one's moral values may potentially take a toll on relationship quality. As attitudes toward pornography become more accepting in the United States (Lykke & Cohen, 2015;Price, Patterson, Regnerus, & Walley, 2016), it is possible that any moderating effect of moral incongruence will be attenuated. Conversely, if the attitudes of young Americans toward pornography are not changing tremendously (see Price et al, 2016) even as pornography use continues to increase, it may be that more Americans will find themselves in the situation where they are violating their own consciences in viewing pornography, thus holding greater consequences for mental health (Grubbs et al, 2015b;Perry, 2017b) or intimate relationships.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead those same communities to having very different views toward various moral issues, like porn, for instance. Consistently, studies find that the religious groups with which individuals affiliate, their religious beliefs, and their religious behaviors routinely influence their views toward porn (Carroll et al, 2008;Lykke & Cohen, 2015;Patterson & Price, 2012;Sherkat & Ellison, 1997) and various other moral issues (Hoffman, Ellison, & Bartkowski, 2016;Perry, 2015;Whitehead & Perry, 2016). Therefore, it is important to examine the content and character of religiosity at the state-level, rather than only examining aggregated measures of how religious individuals perceive themselves to be.…”
Section: Introductionmentioning
confidence: 86%
“…Because we feel there is little scientific evidence to support the notion that essential race (and sex) differences drive the differential consumption patterns, and because our analyses look at adults and control for relevant sociodemographic characteristics, we feel that theories emphasizing broader cultural influences on sexual norms and behaviors are more promising. Specifically, we propose the most likely source of these differences are the divergent historical and subcultural experiences with pornography at the community level that have influenced white Americans to find pornography more morally objectionable than black Americans (see Lykke & Cohen, 2015;Patterson & Price, 2012;Sherkat & Ellison, 1997;Wood & Hughes, 1984). Pornography has never been a key moral issue for the black community, and thus, black Americans would predictably hold fewer internalized norms against viewing pornography, and this would explain their greater likelihood of viewing pornography relative to whites.…”
Section: Discussionmentioning
confidence: 99%
“…Black communities, by contrast, have never targeted pornography use as a key moral issue worth opposing (Wood & Hughes, 1984), preferring instead to focus on more immediate, structural issues (Pattillo-McCoy, 1998;Shelton & Emerson, 2012). Thus, it is unsurprising that studies have historically found black Americans being less likely than white Americans to believe pornography should be illegal for all ages or that it causes a societal breakdown in morals (Lykke & Cohen, 2015;Patterson & Price, 2012;Sherkat & Ellison, 1997;Wood & Hughes, 1984).…”
Section: Theorizing the Link Between Race Pornography Viewership Anmentioning
confidence: 99%
See 1 more Smart Citation